MG-129 The development of a genetic newborn screening assay for permanent hearing loss using blood spots – a collaboration between newborn screening ontario (NSO) and the infant hearing program (IHP). (4th December 2015) - Bulman, Dennis E; Yeh, Edward; Durie, Danielle; McClelland, Shannon; Theriault, Mylene; Liyanage, Hema; Higgins, Lauren; Pluscauskas, Michael; Weber, Stacey; Hyde, Martyn L; Chakraborty, Pranesh
Abstract : Background: The Ontario Infant Hearing Program identifies babies born with, or at risk for, permanent hearing impairment. The current method of audiometric screening may be limited in detecting forms of hearing impairment, which are clinically silent in the newborn but may become apparent in the pre-school period. Objectives: To determine the prevalence of detectable CMV genomes and determine the disease allele frequencies for selected mutations in GJB2, GJB6, SLC26A and MT-RNR1 in Ontario Newborns. Methods: 10, 000 historical blood spots were screened to determine the first Ontario population-based data regarding the prevalence of congenital CMV and the allele frequencies of the common mutations in GJB2, GJB6, SLC26A and MT-RNR1 which are associated with hearing impairment. A 2-part assay was developed to screen newborn dry blood spots – 1) a multiplex genotyping assay based on Sequenom® iPlex technology and 2) a multiplex qPCR assay to detect and quantify CMV, as well as to detect a known deletion in GJB6. Results: We detected CMV genomes in 0.6% of blood spots screened. Disease allele frequencies were determined and those for GJB2/GJB6 as well as SLC26A were found not to be in Hardy-Weinberg equilibrium (HWE), with non-assortative mating postulated to be the major contributing factor. Lastly, the population frequency of MT-RNR1 alleles responsible for sensitivity to aminoglycoside antibiotics was 1.7%. Conclusions: In the future, possible implementation of newborn blood spot screening for hearing impairment would enhance the current ascertainment of infants at risk for hearing impairment and introduce an etiologic component to hearing screening in Ontario.